Feasibility studies on the selective separation of fission palladium(II) by isoHex-BTP/SiO2-P adsorbent from HLLW. Issue 8 (3rd August 2017) - Liu, Ruiqin; Zou, Qing; Zu, Jianhua; Wei, Yuezhou; Ding, Youqian; Zhao, Yaping
ABSTRACT: Aiming at the selective recovery of fission palladium(II) from high-level liquid waste (HLLW), the silica/polymer (SiO2 -P)-based iso Hex-BTP adsorbent ( iso Hex-BTP/SiO2 -P) was synthesized by impregnating complexing agent iso Hex-BTP into the multiporous SiO2 -P inert support. The feasibility of separation of Pd(II) from HLLW by iso Hex-BTP/SiO2 -P was evaluated by batch experiment method. The results showed that iso Hex-BTP/SiO2 -P exhibited much higher adsorption selectivity for Pd(II) than the other fission products, even Am(III) and Pu(IV) presented in HLLW. The ideal nitric acid concentration for the adsorption of Pd(II) by the adsorbent was shown to be ≥2 mol dm –3 . The adsorption of Pd(II) fits well to the pseudo-second-order kinetic model and Langmuir isotherm model. Quantitative Pd(II) desorption was achieved by using 0.5 mol dm −3 SC(NH2 )2 - 0.1 mol dm −3 HNO3 solution.